Heart Failure in Elderly Patients: Medical Management, Therapies and Biomarkers - Paulina Nadziakiewicz; Wioletta Szczurek-Wasilewicz; Bożena Szyguła-Jurkiewicz (Pharmaceuticals)
Heart failure (HF) is a common condition and one of the main morbidity and mortality factors in elderly patients. The incidence of HF progressively increases with age, reaching >10% in those aged 70 years or over. In the elderly population, both the diagnosis and the management of HF prove challenging, often requiring specialized care and a multidisciplinary approach. In seniors, atypical presentation of HF is much more common than in younger patients; thus, a holistic assessment with biomarkers related to HF allows for early diagnosis and accurate risk stratification in this group of patients. This article reviews the clinical and diagnostic differences in elderly patients with HF, highlighting the presence of comorbidities, frailty, cognitive impairment, and polypharmacy, as well as discussing potential biomarkers that may have clinical application in this population.